Improving Daytime Sleepiness in Children and Adolescents With Narcolepsy: A Quality Improvement Initiative - Gurbani, Neepa; Dye, Thomas J.; Simmons, Danielle M.; Pascoe, John E.; Bibbins, Jennifer; Cole, Amy; Mullen, Lisa; Schuler, Christine L.; Simakajornboon, Narong (Pediatric neurology, 2025)
We sought to improve daytime sleepiness in pediatric narcolepsy and aimed to increase the percentage of pediatric patients with at least 30% improvement on the Epworth Sleepiness Scale (ESS), compared with baseline. We convened a multidisciplinary team and used standard quality improvement (QI) methods to track and improve daytime sleepiness. Interventions included staff reminders, previsit planning tool enhancement, tracking missed visits and time to follow-up, contacting patients with missed visits, and following prescription records. We conducted Plan-Do-Study-Act cycles and created run charts to track progress. From August 2019 to July 2024, 105 patients with narcolepsy were seen in sleep clinic. Several process improvements were implemented. ESS completion rate increased from 60% to 75%. The proportion of patients with a clinician-documented time frame for follow-up in the electronic health record increased from 44% to 86% initially and subsequently was maintained at 77%. The percentage of patients with narcolepsy who returned to clinic within 60 days of the requested follow-up date fell during the coronavirus disease 2019 pandemic; it has since remained approximately 68%. Initially, ∼72% of patients filled prescriptions. The percentage of patients with a 30% improvement in the ESS, compared with the baseline, improved from 47% to 62%. In addition, the percentage of patients with a 10% increase in Pediatric Quality of Life Inventory screen scores was maintained at approximately 75%. Using QI methods and various interventions, we improved daytime sleepiness scores in children and adolescents with narcolepsy. Multifaceted and creative strategies are still needed to address residual sleepiness, improve quality of life, and maximize patient safety.